Simultaneous Consecutive Interpreting: A New Technique Put to the Test - Hamidi, Miriam; Pöchhacker, Franz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThe paper reports a small-scale experimental study to test the viability or even superiority of technology-assisted consecutive interpreting as a new working method for conference interpreters. In this technique, pioneered in 1999 by an EU staff interpreter, a digital voice recorder is used to record the original speech which the interpreter then plays back into earphones and renders in the simultaneous mode. The performances of three experienced professional interpreters (French-German) in the conventional consecutive and the ‘simultaneous consecutive’ mode were assessed and compared on the basis of transcript analysis, self-assessment and audience response. Our findings suggest that simultaneous consecutive permits enhanced interpreting performances, as reflected in more fluent delivery, closer source–target correspondence, and fewer prosodic deviations. Though the interpreters’ personal working experience and preferences appeared to have a significant influence on their performance, all three subjects easily adopted the technology-assisted interpreting mode and considered it a viable technique.